An Oversimplified Corrosion Inhibition Experiment Suitable for the Development of the Laboratory Practice for Undergraduate Students - Pavel Anatolyevich Nikolaychuk; Natalya Viktorovna Maltseva; Marina Valeryevna Lebedeva; Denis Vladimirovich Kozlov (Orbital: The Electronic Journal of Chemistry, 2025)
An oversimplified corrosion inhibition experiment suitable for the laboratory practice for undergraduate students was developed. The different simplifications to the standard procedure of the corrosion inhibition experiment were tested. Using the examples of steel corrosion inhibition in sulfuric acid by sodium tungstate, and in hydrochloric acid by succinic acid, it was shown that the obtained results remain representative even if the experiment is performed very roughly and inaccurately. During the standard laboratory 3-hour session, both the gravimetric and electrochemical experiments in uninhibited medium with three different inhibitor concentrations could be performed by the students. The typical methodical instructions for the students and instructors were developed. The proposed laboratory experiment was tested during an academic year with the master-level students in Novosibirsk State University.